If we have the same educational level, why do not we earn the same? Salary differentiation in Santiago de Cali - Jiménez Restrepo Diana Marcela; Pino Garcés Anderson (Sociedad y Economía, 2018)
The purpose of this paper is to calculate the salary difference between men and women, in Cali, Colombia, considering the educational level. In order to achieve this, a salary difference index was created and estimated, using data from the Employment and Quality of Life survey conducted by the Mayor’s Office of Cali and the Ministry of Labor. The results show that, regardless of the educational level presented by the employed in this city, women earn a weekly salary lower than that of men; and only in the case of secondary school, this inequality becomes lower.